Weakening and structural temper. A new approach to the interpretation of results of physico-chemical tests on Medieval pottery pastes - Rzeźnik, Paweł; Stoksik, Henryk (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2008)
The archaeological literature on the technology of ancient ceramics abounds in statements which express the conviction that various non-plastic materials added to the clay were used mostly to increase the mechanical durability of the pottery. Integrated physico-chemical analyses and archaeological studies of Medieval ceramics discovered in Silesia, found to contain materials like graphite or grog, have proved this to be a simplified viewpoint. According to the new approach, such non-plastic additions to the clay were aimed mostly at enhancing the workability of the mass and improving its structural qualities. In this way it was possible to obtain fabrics suitable for moulding big-sized thick-walled vessels and for wheel-throwing thin-walled ceramics. This discovery has resolved a question archaeologists have wrestled with for decades, namely, why Moravian potters were so inclined to use recipes containing graphite and how they managed to form amazingly big vessels, a rarity in Central European pottery of their time
ill. ; 24 cm
Keywords: graphittonkeramik; ceramics with grog; middle ages; Silesia; physico-chemical analyses; temper